Negative-expansion and high-thermal-conductivity electronic packaging material Zn2-xNixP2O7 and preparation method thereof
By preparing Zn2-xNixP2O7 electronic packaging material, the problems of complex preparation, high cost and thermal expansion mismatch of silicon micropowder are solved, and the effects of high thermal conductivity and negative thermal expansion coefficient are achieved, and the performance of electronic packaging materials is improved.
Patent Information
- Application Number
- CN202411603499.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-28
AI Technical Summary
The existing electronic packaging material silicon micropowder preparation process is complex, has high cost, low thermal conductivity and mismatch, resulting in mechanical deformation problems during use of the integrated circuit.
Zn2-xNixP2O7 (x=0.5, 1.0, 1.5) was used as negative expansion and high-thermal conductive electronic packaging material, and prepared by mixing ZnO, NiO and ammonium salt phosphates, grinding, drying, sintering and other steps.
An electronic packaging material with low preparation cost, high thermal conductivity and negative thermal expansion coefficient is realized, which effectively improves the thermal conductivity of the epoxy resin and reduces its thermal expansion coefficient, solving the problem of thermal expansion mismatch.
Smart Images

Figure CN119528102A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing an electronic packaging material, and in particular to a negative expansion, high thermal conductivity electronic packaging material Zn 2-x Ni x P2O7 and its preparation method. Background Art
[0002] In electronic packaging, epoxy molding compounds need to have the following characteristics: small thermal expansion coefficient; small shrinkage stress during curing shrinkage; high thermal conductivity; low water absorption; strong flame retardancy; low cost; high dimensional stability; ability to prevent resin from overflowing the parting line of the molding mold; reduce the heat release during the cross-linking curing reaction of the resin; and improve the heat resistance of the cured product. In order to meet these requirements, epoxy molding compounds are usually doped with inorganic fillers in the resin matrix. The main filler currently used is silicon micropowder.
[0003] However, the preparation process of silicon micropowder is complex, expensive and energy-intensive, requiring a high temperature of 2500°C, which results in large carbon emissions. Its high-end products are mainly monopolized by countries such as the United States and Japan. In addition, the thermal conductivity of silicon micropowder is low, only 1.0W / m·K, while its intrinsic thermal expansion coefficient is 0.5×10 -6 / K, showing positive expansion. The thermal expansion coefficient of packaging materials is usually 30×10 -6 / K to 300×10 -6 / K range, the thermal expansion coefficient of the chip is 2.6×10 -6 / K to 4.5×10 -6 / K, while the thermal expansion coefficient of the package substrate is 16.7×10 -6 / K to 29.3×10 -6 / K. The thermal expansion coefficients of these different parts are seriously mismatched.
[0004] Although epoxy molding compound formed by mixing silicon powder with epoxy resin can fill the gap between the chip and the substrate, it cannot effectively solve the problem of thermal expansion mismatch, which can easily lead to mechanical deformation problems such as delamination, cracking and warping of integrated circuits during subsequent use. Summary of the invention
[0005] The purpose of the present invention is to provide a negative expansion, high thermal conductivity electronic packaging material Zn 2-x Ni x P2O7 and its preparation method. The preparation method of the present invention is simpler than silicon micropowder, has low cost, and has controllable preparation scale. The prepared product has a negative thermal expansion coefficient and high thermal conductivity, can be used as a bottom filler for electronic packaging, effectively improves the thermal conductivity of epoxy resin, and reduces its thermal expansion coefficient.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A negative expansion, high thermal conductivity electronic packaging material Zn 2-x Ni x P2O7, chemical formula is Zn 2-x Ni x P2O7, where the values of x are 0.5, 1.0, and 1.5.
[0008] A negative expansion, high thermal conductivity electronic packaging material Zn 2-x Ni x The preparation method of P2O7 comprises the following steps:
[0009] Step (1): According to the chemical formula Zn 2-x Ni x P2O7: Mixed samples are obtained by mixing ZnO, NiO and ammonium phosphate, where the values of x are 0.5, 1.0 and 1.5;
[0010] Step (2): putting the mixed sample into an agate mortar and adding a grinding additive for grinding, and then drying to obtain a dried sample;
[0011] Step (3): placing the dried sample in a muffle furnace, heating it from room temperature to 750-950° C. at a heating rate of 5° C. / min, keeping it at that temperature for 2-5 hours, and then cooling it to room temperature at a cooling rate of 5° C. / min to obtain a precursor;
[0012] Step (4): wet-grind and dry the precursor, press it into tablets, and place it in a muffle furnace. Heat it from room temperature to 850-950°C at a heating rate of 5°C / min, keep it at that temperature for 2-5h, and then cool it to room temperature at a cooling rate of 5°C / min to obtain a sintered sample.
[0013] Furthermore, the ammonium phosphate in step (1) is selected from NH4H2PO4 or (NH4)2HPO4.
[0014] Furthermore, the grinding additive in step (2) is water, ethanol, ethylene glycol or acetone.
[0015] Furthermore, the grinding time in step (2) is 1 to 2 hours.
[0016] Furthermore, the drying process in step (2) is to place the product in a forced air drying oven for 2 to 3 hours.
[0017] Furthermore, the tableting process in step (4) is to place the tablet in a tablet press mold and maintain it at a pressure of 15 MPa for 3 minutes.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The present invention adopts the solid phase method to prepare Zn 2-x Ni x The preparation method of P2O7 (x=0.5, 1.0, 1.5) is simple, low-cost, and controllable in scale. The prepared product has a negative thermal expansion coefficient and a high thermal conductivity, and can be used as a bottom filler for electronic packaging, effectively improving the thermal conductivity of epoxy resin and reducing its thermal expansion coefficient.
[0020] (2) The negative expansion coefficient of the existing packaging material Ni2P2O7 (-35.8×10 -6 / K) occurs in the high temperature range (547~587℃), and the temperature range is very narrow, only 40℃. The present invention adopts Ni atoms to replace Zn atoms to regulate thermal expansion, which not only effectively increases the negative expansion coefficient and reduces the phase transition temperature of Ni2P2O7, but also greatly broadens the negative thermal expansion temperature range.
[0021] (3) In the preparation process of the present invention, since the ammonium salt phosphate in the raw material releases gas during the sintering process, resulting in voids in the sample, pre-sintering is first used to remove the pores, and then tableting and calcination are used to make the sample react more fully.
[0022] (4) Zn prepared by the present invention 1.5 Ni 0.5 The negative thermal expansion coefficient of P2O7 reaches -161.6ppm / K in the temperature range of 123-164℃. The thermal conductivity is the highest at room temperature, with a value of 2.3W·m -1 ·K -1 , which is twice that of traditional electronic packaging filler silicon micropowder.
[0023] (5) When the ZnNiP2O7 filler prepared by the present invention is added to epoxy resin, the thermal expansion coefficient is reduced by 44.8%, and the thermal conductivity is also significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 XRD patterns of samples prepared in Examples 1 to 3 of the present invention;
[0025] Figure 2 (a) shows the Zn prepared in Example 1 of the present invention. 1.5 Ni 0.5 The refined X-ray diffraction pattern of P2O7;
[0026] FIG2( b ) is a refined X-ray diffraction pattern of ZnNiP2O7 prepared in Example 2 of the present invention;
[0027] Figure 3 (a) shows the Zn prepared in Example 1 of the present invention. 1.5 Ni 0.5Thermal expansion coefficient curves of P2O7 and ZnNiP2O7 sintered ceramics prepared in Example 2;
[0028] Figure 3(b) shows the Zn prepared in Example 3 of the present invention. 0.5 Ni 1.5 Thermal expansion coefficient curve of P2O7 sintered ceramics;
[0029] Figure 4 The thermal conductivity curves of the fillers of the samples prepared in Examples 1 to 3 of the present invention are as follows;
[0030] Figure 5 Thermal expansion curves of epoxy molding compounds prepared using samples prepared in Examples 1 to 3 of the present invention and epoxy resin and epoxy molding compounds without fillers;
[0031] Figure 6 The thermal conductivity curves of epoxy molding compounds prepared using the samples prepared in Examples 1 to 3 of the present invention and epoxy resin and epoxy molding compounds without fillers are shown. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0033] Example 1: A negative expansion, high thermal conductivity electronic packaging material Zn 2-x Ni x The preparation method of P2O7 is as follows:
[0034] Step (1): According to the chemical formula Zn 1.5 Ni 0.5 P2O7 mixed ZnO, NiO and NH4H2PO4 to obtain a mixed sample;
[0035] Step (2): the mixed sample was placed in an agate mortar and ethanol was added for grinding for 1 hour, and then placed in a forced air drying oven for drying for 2 hours to obtain a dried sample;
[0036] Step (3): placing the dried sample in a muffle furnace, heating from room temperature to 750°C at a heating rate of 5°C / min, keeping the temperature for 5 hours, and then cooling to room temperature at a cooling rate of 5°C / min to obtain a precursor;
[0037] Step (4): The precursor was placed in an agate mortar for wet grinding, then dried, placed in a tablet press mold, kept at a pressure of 15 MPa for 3 minutes, and then placed in a muffle furnace, heated from room temperature to 850°C at a heating rate of 5°C / min, kept warm for 5 hours, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a sintered sample Zn 1.5 Ni 0.5 P2O7.
[0038] Example 2: A negative expansion, high thermal conductivity electronic packaging material Zn 2-x Ni x The preparation method of P2O7 is as follows:
[0039] Step (1): mixing ZnO, NiO and NH4H2PO4 according to the chemical formula ZnNiP2O7 to obtain a mixed sample;
[0040] Step (2): the mixed sample was placed in an agate mortar and ethanol was added for grinding for 2 h, and then placed in a forced air drying oven for drying for 2.5 h to obtain a dried sample;
[0041] Step (3): placing the dried sample in a muffle furnace, heating it from room temperature to 800°C at a heating rate of 5°C / min, keeping it at that temperature for 4 hours, and then cooling it to room temperature at a cooling rate of 5°C / min to obtain a precursor;
[0042] Step (4): Place the precursor in an agate mortar for wet grinding, then dry it, place it in a tablet press mold, keep it at a pressure of 15 MPa for 3 minutes to form a tablet, then place it in a muffle furnace, heat it from room temperature to 900°C at a heating rate of 5°C / min, keep it warm for 3 hours, and then cool it to room temperature at a cooling rate of 5°C / min to obtain a sintered sample ZnNiP2O7.
[0043] Example 3: A negative expansion, high thermal conductivity electronic packaging material Zn 2-x Ni x The preparation method of P2O7 is as follows:
[0044] Step (1): According to the chemical formula Zn 0.5 Ni 1.5 P2O7 mixed ZnO, NiO and NH4H2PO4 to obtain a mixed sample;
[0045] Step (2): the mixed sample was placed in an agate mortar and ethanol was added for grinding for 1.5 h, and then placed in a forced air drying oven for drying for 3 h to obtain a dried sample;
[0046] Step (3): placing the dried sample in a muffle furnace, heating from room temperature to 780°C at a heating rate of 5°C / min, keeping the temperature for 4 hours, and then cooling to room temperature at a cooling rate of 5°C / min to obtain a precursor;
[0047] Step (4): The precursor was placed in an agate mortar for wet grinding, then dried, placed in a tablet press mold, kept at a pressure of 15 MPa for 3 minutes, and then placed in a muffle furnace, heated from room temperature to 860°C at a heating rate of 5°C / min, kept at this temperature for 5 hours, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a sintered sample Zn 0.5 Ni 1.5P2O7.
[0048] Example 4: A negative expansion, high thermal conductivity electronic packaging material Zn 2-x Ni x The preparation method of P2O7 is as follows:
[0049] Step (1): According to the chemical formula Zn 0.5 Ni 1.5 P2O7: Mix ZnO, NiO and (NH4)2HPO4 to obtain a mixed sample;
[0050] Step (2): the mixed sample was placed in an agate mortar and water was added for grinding for 1 hour, and then placed in a forced air drying oven for drying for 2 hours to obtain a dried sample;
[0051] Step (3): placing the dried sample in a muffle furnace, heating it from room temperature to 900°C at a heating rate of 5°C / min, keeping it at that temperature for 3h, and then cooling it to room temperature at a cooling rate of 5°C / min to obtain a precursor;
[0052] Step (4): The precursor was placed in an agate mortar for wet grinding, then dried, placed in a tablet press mold, kept at a pressure of 15 MPa for 3 minutes, and then placed in a muffle furnace, heated from room temperature to 950°C at a heating rate of 5°C / min, kept warm for 2 hours, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a sintered sample Zn 0.5 Ni 1.5 P2O7.
[0053] Example 5: A negative expansion, high thermal conductivity electronic packaging material Zn 2-x Ni x The preparation method of P2O7 is as follows:
[0054] Step (1): According to the chemical formula Zn 1.5 Ni 0.5 P2O7: Mix ZnO, NiO and (NH4)2HPO4 to obtain a mixed sample;
[0055] Step (2): the mixed sample was placed in an agate mortar and ethylene glycol was added for grinding for 1 hour, and then placed in a forced air drying oven for drying for 2 hours to obtain a dried sample;
[0056] Step (3): placing the dried sample in a muffle furnace, heating from room temperature to 950°C at a heating rate of 5°C / min, keeping the temperature for 2h, and then cooling to room temperature at a cooling rate of 5°C / min to obtain a precursor;
[0057] Step (4): The precursor was placed in an agate mortar for wet grinding, then dried, placed in a tablet press mold, kept at a pressure of 15 MPa for 3 minutes, and then placed in a muffle furnace, heated from room temperature to 850°C at a heating rate of 5°C / min, kept warm for 4 hours, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a sintered sample Zn 1.5 Ni 0.5 P2O7.
[0058] Example 6: A negative expansion, high thermal conductivity electronic packaging material Zn 2-x Ni x The preparation method of P2O7 is as follows:
[0059] Step (1): mixing ZnO, NiO and (NH4)2HPO4 according to the chemical formula ZnNiP2O7 to obtain a mixed sample;
[0060] Step (2): the mixed sample was placed in an agate mortar and acetone was added for grinding for 1 hour, and then placed in a forced air drying oven for drying for 2 hours to obtain a dried sample;
[0061] Step (3): placing the dried sample in a muffle furnace, heating from room temperature to 930°C at a heating rate of 5°C / min, keeping the temperature for 2h, and cooling to room temperature at a cooling rate of 5°C / min to obtain a precursor;
[0062] Step (4): Place the precursor in an agate mortar for wet grinding, then dry it, place it in a tablet press mold, keep it at a pressure of 15 MPa for 3 minutes, and then place it in a muffle furnace, heat it from room temperature to 920°C at a heating rate of 5°C / min, keep it warm for 3 hours, and then cool it to room temperature at a cooling rate of 5°C / min to obtain a sintered sample ZnNiP2O7.
[0063] Figure 1 The sintered sample Zn 1.5 Ni 0.5 P2O7, ZnNiP2O7 and Zn 0.5 Ni 1.5 The XRD spectrum of P2O7 shows that the main peak of the sample is at 29.5°, and the other two peaks are at 25.5° and 44° respectively. Using the existing Zn2P2O7 crystal information and diffraction data, the crystal structure model of the sample was optimized using the Rietveld method and Fullprof software. 1.5 Ni 0.5The XRD patterns of P2O7 and ZnNiP2O7 were refined, and finally the X-ray diffraction patterns of the refined samples were compared with the standard XRD patterns generated by Fullprof software, as shown in Figure 2(a) and Figure 2(b). The figures show that the theoretical X-ray diffraction patterns are consistent with the calculated patterns, which shows that Zn 1.5 Ni 0.5 P2O7 and ZnNiP2O7 samples were successfully synthesized.
[0064] The sintering conditions were 1073K (800℃), 20min, and 50MPa. 2-x Ni x P2O7 (x = 0.5, 1.0, 1.5) powder was pressed into ceramic sheets using a spark sintering furnace and the following performance tests were performed:
[0065] (1) Thermal expansion coefficient
[0066] The thermal expansion test of the ceramic sheet is shown in Figure 3(a) and Figure 3(b). 2-x Ni x In the ceramic sheets sintered with P2O7 (x = 0.5, 1.0, 1.5), Zn 1.5 Ni 0.5 The negative expansion phenomenon of P2O7 ceramic sheets is the most significant. In the temperature range of 396-437K, the thermal expansion coefficient is -161.6×10 -6 / K; The negative expansion phenomenon of ZnNiP2O7 ceramic occurs in the temperature range of 392-462K, and the thermal expansion coefficient is -12.9×10 -6 / K; Zn 0.5 Ni 1.5 The thermal expansion coefficient of P2O7 ceramic sheet at 528-585K is -8.5×10 -6 / K.
[0067] The linear thermal expansion coefficient of spherical SiO2 is 0.5×10 -6 / K, positive value, Zn 2-x Ni x The thermal expansion coefficients of ceramic sheets sintered with P2O7 (x = 0.5, 1.0, 1.5) are all negative. Compared with spherical SiO2, Zn 2-x Ni x P2O7 sintered ceramic sheets have good negative expansion properties.
[0068] (2) Thermal conductivity
[0069] λ is thermal conductivity, unit is W·m -1 ·K -1The thermal conductivity can be calculated by the following method: Use a laser thermal conductivity meter to measure the thermal diffusion coefficient D (unit: mm 2 / s), and the density ρ (in g / cm 3 ), and the specific heat capacity Cv (in J·g) was calculated by the Dulong-Petit law -1 ·K -1 ). Multiplying these three together, we can get the thermal conductivity λ. The thermal conductivity data is as follows: Figure 4 As shown. At room temperature, Zn 1.5 Ni 0.5 The thermal conductivity of P2O7 is 2.30 W·m -1 ·K -1 The thermal conductivity of ZnNiP2O7 is 1.54 W·m -1 ·K -1 , Zn 0.5 Ni 1.5 The thermal conductivity of P2O7 is 3.07 W·m -1 ·K -1 , which is higher than that of spherical SiO2. The thermal conductivity of spherical SiO2 at 300K is 1.1 W·m -1 ·K -1 .
[0070] Figure 4 In Zn 1.5 Ni 0.5 The thermal conductivity of P2O7 and ZnNiP2O7 shows a trend of first decreasing and then leveling off as the temperature increases. As the temperature increases, the lattice vibration intensifies, the collision and scattering between phonons increase, which reduces the phonon mean free path and reduces the thermal conductivity. 0.5 Ni 1.5 The thermal conductivity of P2O7 decreases first and then increases with increasing temperature. When the temperature increases, the phonon scattering in the lattice increases, thereby increasing the thermal resistance and causing the thermal conductivity to decrease. As the temperature further increases, the electrons in the material are excited to a higher energy level. These excited electrons contribute to heat conduction. At high temperatures, the contribution of these electrons to thermal conductivity exceeds the thermal resistance caused by lattice vibration, causing the thermal conductivity to rise again.
[0071] Epoxy molding compounds were prepared by curing reaction of epoxy resin and curing agent. First, pure epoxy resin molding compounds without fillers were prepared as control samples, and then 60% by mass fraction of Zn was added. 1.5 Ni 0.5 P2O7, ZnNiP2O7 and Zn 0.5 Ni 1.5 P2O7 plastic packaging material, and the following performance tests:
[0072] (1) Thermal expansion of epoxy molding compound
[0073] Thermal expansion data such as Figure 5 As shown, it can be seen that the negative expansion material Zn 2-x Ni x P2O7 (x=0.5, 1.0, 1.5) can effectively reduce the huge thermal expansion coefficient of epoxy resin. When high thermal conductivity fillers are added to the molding compound, the thermal conductivity of the molding compound as a whole is increased, thereby effectively dispersing the heat and avoiding the unevenness of the local temperature of the resin during the heating process, thereby inhibiting thermal expansion. Secondly, when the powdered filler is added to the epoxy resin, the filler powder is a harder particle, and the filler is embedded in the resin to form a bone-like structure, which inhibits the thermal expansion of the resin during the heating process, thereby reducing the thermal expansion coefficient of the molding compound.
[0074] (2) Thermal conductivity of epoxy molding compound
[0075] The thermal diffusion coefficient is measured by laser thermal conductivity meter, the density is calculated by Archimedes method, and the specific heat capacity is measured by differential scanning calorimeter. The thermal conductivity of the plastic packaging material is obtained by multiplying the three. Figure 6 , it can be seen that the high thermal conductivity of Zn 2-x Ni x P2O7 (x=0.5, 1.0, 1.5) can effectively increase the thermal conductivity of epoxy resin. The filler has high thermal conductivity. When the filler is evenly distributed in the epoxy resin, its high thermal conductivity property is extended to the entire molding compound, thereby improving the thermal conductivity of the entire molding compound.
Claims
1. A negative expansion, high thermal conductivity electronic packaging material Zn 2-x Ni x P2O7, characterized in that The chemical formula is Zn 2-x Ni x P2O7, where the values of x are 0.5, 1.0, and 1.
5.
2. A negative expansion, high thermal conductivity electronic packaging material Zn according to claim 1 2-x Ni x The preparation method of P2O7 is characterized in that: The following steps are involved: Step (1): According to the chemical formula Zn 2-x Ni x P2O7: Mixed samples are obtained by mixing ZnO, NiO and ammonium phosphate, where the values of x are 0.5, 1.0 and 1.5; Step (2): putting the mixed sample into an agate mortar and adding a grinding additive for grinding, and then drying to obtain a dried sample; Step (3): placing the dried sample in a muffle furnace, heating it from room temperature to 750-950° C. at a heating rate of 5° C. / min, keeping it at that temperature for 2-5 hours, and then cooling it to room temperature at a cooling rate of 5° C. / min to obtain a precursor; Step (4): wet-grind and dry the precursor, press it into tablets, and place it in a muffle furnace. Heat it from room temperature to 850-950°C at a heating rate of 5°C / min, keep it at that temperature for 2-5h, and then cool it to room temperature at a cooling rate of 5°C / min to obtain a sintered sample.
3. A negative expansion, high thermal conductivity electronic packaging material Zn according to claim 2 2-x Ni x The preparation method of P2O7 is characterized in that: The ammonium phosphate in step (1) is selected from NH4H2PO4 or (NH4)2HPO4.
4. A negative expansion, high thermal conductivity electronic packaging material Zn according to claim 1 2-x Ni x The preparation method of P2O7 is characterized in that: The grinding additive in step (2) is water, ethanol, ethylene glycol or acetone.
5. A negative expansion, high thermal conductivity electronic packaging material Zn according to claim 2 2-x Ni x The preparation method of P2O7 is characterized in that: The grinding time in step (2) is 1 to 2 hours.
6. A negative expansion, high thermal conductivity electronic packaging material Zn according to claim 2 2-x Ni x The preparation method of P2O7 is characterized in that: The drying process described in step (2) is to place the product in a forced air drying oven and dry it for 2 to 3 hours.
7. A negative expansion, high thermal conductivity electronic packaging material Zn according to claim 2 2-x Ni x The preparation method of P2O7 is characterized in that: The tableting process in step (4) is to place the tablet in a tablet press mold and maintain it at a pressure of 15 MPa for 3 minutes.